Analisis Kelayakan Investasi Penambahan Peralatan Makan pada Rumah Padat Karya Cafe Viaduct Gubeng di Surabaya Tahun 2024-2029 - Iin Widiastutik (Seminar Nasional Manajemen, 2026)
This study aims to analyze the financial feasibility of investment in additional dining equipment at Rumah Padat Karya Cafe Viaduct Gubeng, Surabaya, for the period 2024–2029. This café operates as a social entrepreneurship unit that emphasizes community empowerment alongside financial sustainability. The research employed a quantitative descriptive method using primary data from interviews and observations, and secondary data from financial reports. Investment feasibility was analyzed using Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR) with a discount rate of 12 percent. The results show that the investment is financially feasible, indicated by a Payback Period of 1 year and 7 months, a positive NPV of IDR 67,073,766, and an IRR of 85.08 percent, which exceeds the required rate of return. These findings imply that the investment supports both financial viability and the sustainability of social entrepreneurship initiatives. Keywords: investment feasibility; Payback Period; Net Present Value; Internal Rate of Return; social entrepreneurship